2015
DOI: 10.1002/eco.1706
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between vegetation type, peat hydraulic conductivity, and water table dynamics in mountain fens

Abstract: The ecohydrologic function of fens is characterized by feedbacks between biological and hydrologic processes. Vegetation composition is one important factor that is both responsive to the site hydrologic regime and, by providing the organic material that determines peat hydrophysical properties, influences hydrologic conditions. In this study, we investigated the relationship between vegetation type and peat soil hydraulic conductivity in fen wetlands within the Rocky Mountain National Park, Colorado. We used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
(50 reference statements)
4
9
0
Order By: Relevance
“…Mean hydraulic conductivity decreases when the computed region size becomes smaller, for each direction and each sample (Supplementary section B2). In-situ measurements, conducted by infiltration (Table 2), give an average of 10 -5 m.s -1 , which is in the same order of magnitude as previously published field measurements (Crockett et al, 2016) and computed values (McCarter & Price, 2012). Analogous values for vertical hydraulic conductivity have been found in the literature at kzz ≈10 -2 m.s -1 (Päivänen, 1973;Crockett et al, 2016;Golubev et al, 2021).…”
Section: [Figures 8 and 9 Location]supporting
confidence: 80%
See 2 more Smart Citations
“…Mean hydraulic conductivity decreases when the computed region size becomes smaller, for each direction and each sample (Supplementary section B2). In-situ measurements, conducted by infiltration (Table 2), give an average of 10 -5 m.s -1 , which is in the same order of magnitude as previously published field measurements (Crockett et al, 2016) and computed values (McCarter & Price, 2012). Analogous values for vertical hydraulic conductivity have been found in the literature at kzz ≈10 -2 m.s -1 (Päivänen, 1973;Crockett et al, 2016;Golubev et al, 2021).…”
Section: [Figures 8 and 9 Location]supporting
confidence: 80%
“…In-situ measurements, conducted by infiltration (Table 2), give an average of 10 -5 m.s -1 , which is in the same order of magnitude as previously published field measurements (Crockett et al, 2016) and computed values (McCarter & Price, 2012). Analogous values for vertical hydraulic conductivity have been found in the literature at kzz ≈10 -2 m.s -1 (Päivänen, 1973;Crockett et al, 2016;Golubev et al, 2021). However, other studies showed results of a different order of magnitude for Sphagnum samples, with values under 10 -4 m.s -1 (Hamamoto et al, 2015).…”
Section: [Figures 8 and 9 Location]supporting
confidence: 80%
See 1 more Smart Citation
“…Fens are a common wetland type in mountain regions (Bao, Wang, Pratte, Mackenzie, & Klamt, ; Chagué‐Goff, Mark, & Dickinson, ; Cooper, Chimner, & Merritt, ), occurring in topographies where groundwater flow is slowed or where there is convergence of surface and subsurface flow paths that maintain saturated soils throughout the growing season (Morrison, Westbrook, & Bedard‐Haughn, ; Winter, ; Wolf & Cooper, ). Hydrological behaviour is thus a critical control on mountain fen ecological and biogeochemical function, including water and carbon storage (Crockett, Ronayne, & Cooper, ; Harbert & Cooper, ; Millar, Cooper, Dwire, Hubbard, & von Fischer, ). Mountain fens are expected to be highly sensitive to changing climate as what are thought to be their primary water supplies (precipitation, snowpack) are directly influenced by climate (Lee et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Some fens have water tables that remain near the surface throughout the summer while others experience strong water table declines. Dynamic water tables occur in part because the current and historic fen vegetation composition, which varies widely, influences peat hydraulic parameters (Crockett et al, 2016). Although, a number of intra-fen feedbacks, such as declining hydraulic conductivity with depth (Kvaerner & Kløve, 2008), act to ensure fens do not experience runaway drying during droughts (Waddington et al, 2015).…”
mentioning
confidence: 99%